Signaling Pathway Inhibitors, miRNA, and Nanocarrier-Based Pharmacotherapeutics for the Treatment of Lung Cancer: A Review - Shadab Md; Nabil A. Alhakamy; Shahid Karim; Gamal A Gabr; Mohammad Kashif Iqubal; Samar S. A. Murshid (Pharmaceutics, 2021)
Lung cancer is one of the most commonly diagnosed cancers and is responsible for a large number of deaths worldwide. The pathogenic mechanism of lung cancer is complex and multifactorial in origin. Thus, various signaling pathways as targets for therapy are being examined, and many new drugs are in the pipeline. However, both conventional and target-based drugs have been reported to present significant adverse effects, and both types of drugs can affect the clinical outcome in addition to patient quality of life. Recently, miRNA has been identified as a promising target for lung cancer treatment. Therefore, miRNA mimics, oncomiRs, or miRNA suppressors have been developed and studied for possible anticancer effects. However, these miRNAs also suffer from the limitations of low stability, biodegradation, thermal instability, and other issues. Thus, nanocarrier-based drug delivery for the chemotherapeutic drug delivery in addition to miRNA-based systems have been developed so that existing limitations can be resolved, and enhanced therapeutic outcomes can be achieved. Thus, this review discusses lung cancer’s molecular mechanism, currently approved drugs, and their adverse effects. We also discuss miRNA biosynthesis and pathogenetic role, highlight pre-clinical and clinical evidence for use of miRNA in cancer therapy, and discussed limitations of this therapy. Furthermore, nanocarrier-based drug delivery systems to deliver chemotherapeutic drugs and miRNAs are described in detail. In brief, the present review describes the mechanism and up-to-date possible therapeutic approaches for lung cancer treatment and emphasizes future prospects to bring these novel approaches from bench to bedside.